Business Models and Development Strategies In The Corned Oyster Culinary Business - Arni Arni; Rahmatullah Rahmatullah; Muh Ihsan Said Ahmad; syamsu Rijal; Mustari Mustari (Universitas Negeri Makassar, 2023)
This research aims to determine the business model and development strategy that can be carried out by traditional grilled oyster culinary entrepreneurs in Lajari village so that their business can run well amidst the complex competition between culinary establishments. This research is a type of qualitative research with a Business Model Canvas approach which is described in 9 components combined with consumer desires obtained using empathy maps and SWOT analysis. Data collection techniques with observation, interview, and documentation methods. The results of the research show a SWOT analysis diagram of the strategy direction in